1993
DOI: 10.1111/j.1365-2222.1993.tb00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of steroid‐dependent asthma with recombinant interferon‐gamma

Abstract: We have recently reported that treatment of patients with severe atopic dermatitis with recombinant interferon-gamma (rIFN-gamma) resulted in clinical improvement as well as a reduction of circulating eosinophils. Since IgE-dependent late phase allergic reactions and eosinophilic infiltration are thought to play an important role in the pathogenesis of asthma, we conducted a two centre randomized double-blind placebo-controlled trial of rIFN-gamma in the treatment of steroid-dependent asthma. Patients were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…The results obtained in our study with regard to efficacy agree in part with those obtained by Boguniewicz et al [34], who conducted a double-blind placebo-controlled study in which subcutaneous IFN-γ was administered over 90 days in 20 steroid-dependent asthmatic patients, without significant clinical improvement at the end of the study. …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results obtained in our study with regard to efficacy agree in part with those obtained by Boguniewicz et al [34], who conducted a double-blind placebo-controlled study in which subcutaneous IFN-γ was administered over 90 days in 20 steroid-dependent asthmatic patients, without significant clinical improvement at the end of the study. …”
Section: Discussionsupporting
confidence: 81%
“…Several authors [35,36,37] have shown that IFN-γ administration slows eosinophilia in the airways as well as systemic eosinophilia. Boguniewicz et al [34] found a decrease in peripheral eosinophilia in 31% of cases treated with IFN-γ compared to an increase in eosinophilia in 8.5% of the placebo group. Animal models of bronchial atopic asthma where IFN-γ has been administered intranasally, intratracheally, intravenously or in nebulized form have confirmed this IFN-γ-dependent effect.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have reported that intranasal administration of IFN-␥ effectively inhibited goblet cell metaplasia and AHR in a mouse model (34,35,42). However, no beneficial effects were observed on AHR or symptom scores with IFN-␥ in patients with asthma (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…38 Since IFN-g had no effects on lung function, inhalation of IFN-g was has been evaluated as a possible means for preventing toxicity and enhancing the therapeutic effects of IFN-g administration. 39 Trials on indirect induction of Th1-type immune responses have also been carried out using animal models. The administration of various bacteria that can induce Th1-type immune responses has also been reported to inhibit the development of allergic-induced AHR.…”
Section: Il-4 Antagonistic Mutant Dna Inhibits Allergic Airway Inflammentioning
confidence: 99%